Depression and its associated factors among geriatric population in rural area of south Bihar - Gupta, Animesh; Sinha, Ayushi; Sutradhar, Bapi (International Journal Of Community Medicine And Public Health, 2020)
Background: Depression among elderly has been recognized as one of the major health problems worldwide. However, important life changes that happen as we get older may cause feelings of uneasiness, stress, and sadness. Methods: Community based cross sectional study was conducted among geriatric people (aged above 60 years) residing at rural area of south Bihar. The information regarding sociodemographic characteristics, dietary habits, current working status, any morbid condition and source of income were collected. The level of depression was assessed by using geriatric depression scale short form (GDS SF)-15. Results: The prevalence of depression was 54.6%. Depression was strongly associated with female gender, single status of participants, financial dependent on others and medical illness, which was statistically significant. Conclusions: Depression in geriatric people became a major public health problem in urban as well as rural population. So, there is an urgent need for feasible intervention for geriatric population by the government and health care professional to improve their quality of life and to strengthen the systems for their support.